An active surveillance of anaemia among pregnant women and its association with obstetric history and sanitation in urban areas of Kanpur, Uttar Pradesh - Bano, Firoza; Gahlot, Anju (International Journal Of Community Medicine And Public Health, 2019)
Background: Anaemia is still one of the challenging issues in India in spite of various ongoing nutritional programmes. Very few data have been observed from the state Uttar Pradesh especially from urban areas regarding the status of anaemia during pregnancy. Objectives: To estimate the prevalence of anaemia among pregnant women and its association with the various socio-demographic determinants in urban areas of Kanpur. Methods: Cross-sectional study having total participants of 207 pregnant women were selected by simple random sampling method and interviewed by pretested questionnaire followed by testing haemoglobin level in blood through Sahli’s haemoglobinometer and collected data were analysed using SPSS Version 21.0 and Microsoft Excel 2007. Results: Out of 207 pregnant women 163 were estimated as anaemic. Conclusions: A high prevalence of anaemia was observed which is 78.7%. Adolescent age group, lack of sanitation and worm infestations were detected significant parameters contributing anaemia.